Three‐dimensional kinematics of the canine carpal bones imaged with computed tomography after ex vivo axial limb loading and palmar ligament transection. Issue 6 (9th August 2018) - Neville‐Towle, Jack D.; Tan, Christopher J.; Parr, William C. H.; Walsh, William R.; Johnson, Kenneth A.
Abstract: Objective: To describe normal antebrachiocarpal joint kinematic motion during axial loading and to describe the effect of palmar radiocarpal ligament (PRL) and palmar ulnocarpal ligament (PUL) transection on this motion. Sample population: Ten forelimbs from 5 adult greyhound cadavers. Methods: Limbs were placed in a custom jig and computed tomography images of limbs were obtained in neutral and extended positions. The translation and rotation of the intermedioradiocarpal bone (RCB), ulnar carpal bone, and accessory carpal bone were described relative to the radius through rigid body motion analysis. Kinematic and load analysis was repeated after sequential transection of the PRL and the PUL. Results: Sagittal plane extension with a lesser component of valgus motion was found in all evaluated carpal bones. RCB supination was also detected during extension. Compared with the normal intact limb, transection of either or both the PRL and the PUL did not influence mean translation or rotation data or limb load. However, the transection of the PRL and the PUL increased the variance in rotation data compared with intact limb. Conclusion: This study describes normal antebrachiocarpal kinematics as a foundation for determining carpal functional units. During axial loading, the PRL and the PUL may function to guide consistent motion in extension and flexion as well as pronation and supination. Clinical significance: Three‐dimensional carpal kinematic analyses may improve our understanding of carpal injury and facilitate the development of novel treatments techniques.